2009
DOI: 10.1177/0960327109350664
|View full text |Cite
|
Sign up to set email alerts
|

Acrylamide-induced oxidative stress in human erythrocytes

Abstract: Acrylamide (AA), a widely used industrial chemical, is shown to be neurotoxic, mutagenic and carcinogenic. This study was carried out to investigate the effects of different doses of AA on lipid peroxidation (LPO), haemolysis, methaemoglobin (MetHb) and antioxidant system in human erythrocytes in vitro. Erythrocyte solutions were incubated with 0.10, 0.25, 0.50 and 1.00 mM of AA at 37°C for 1 hour. At the end of the incubation, malondialdehyde (MDA), an end product of LPO, was determined by liquid chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 37 publications
5
25
0
Order By: Relevance
“…cyclophosphatimide treatment has been shown to cause an elevation of micronuclei function in bone marrow of mice and significant decrease in interphase index (MI) (Al-Naimy et al, 2010). This may be due deleterious effect of Cys on bone marrow cell due its free radical producing activity, or it may be due to defect in mitotic spindle composition during cell division (Srivastava et al, 1983) and consequently causing mitosis deficiency (Catalgol et al, 2009). Cyclosporine is thought be decrease breakage of Anaphase Bridge during cell division and DNA damage (Indran et al, 2008).…”
Section: Effect Of S Officinalis On Igg Concentration In Acrylamide mentioning
confidence: 99%
“…cyclophosphatimide treatment has been shown to cause an elevation of micronuclei function in bone marrow of mice and significant decrease in interphase index (MI) (Al-Naimy et al, 2010). This may be due deleterious effect of Cys on bone marrow cell due its free radical producing activity, or it may be due to defect in mitotic spindle composition during cell division (Srivastava et al, 1983) and consequently causing mitosis deficiency (Catalgol et al, 2009). Cyclosporine is thought be decrease breakage of Anaphase Bridge during cell division and DNA damage (Indran et al, 2008).…”
Section: Effect Of S Officinalis On Igg Concentration In Acrylamide mentioning
confidence: 99%
“…Statistical analyses were done using SPSS v. 16.0 (SPSS Inc.,IL, USA). Groups of data were compared with an analysis of variance (ANOVA) followed by Tukey's multiple comparison tests.…”
Section: Discussionmentioning
confidence: 99%
“…An often used and easily detectable parameter for the serum antioxidative and oxidant properties are the total antioxidant status (TAS) and total oxidant status (TOS) [14,15] . It has been showed that the high concentrations of ACR exert deteriorating effects on antioxidant enzyme activities, lipid peroxidation process and haemolysis in human erythrocytes in vitro [16] . Ischemia-modified albumin (IMA) is a novel marker of tissue ischemia [17] .…”
Section: Effects Of Acrylamide Treatment On Oxidant and Antioxidant Lmentioning
confidence: 99%
See 2 more Smart Citations